Buchrezension zu: The Evolution of Imperfection - Jochen Graw (BIOspektrum, 2026)

Buchrezension zu: Free Agents - Jochen Graw (BIOspektrum, 2024)

Aktuell - Kai Papenfort; Jochen Graw; Henning Hintzsche (BIOspektrum, 2023)

Aktuell - Dirk Schüler; Jochen Graw; Henning Hintzsche (BIOspektrum, 2023)

Buchrezension zu: Das Rätsel der Schamanin - Jochen Graw (BIOspektrum, 2023)

Aktuell - Rebekka Biedendieck; Jochen Graw; Henning Hintzsche (BIOspektrum, 2023)

Aktuell - Christine Moissl-Eichinger; Dina Grohmann; Jochen Graw; Henning Hintzsche (BIOspektrum, 2023)

Aktuell - Marc Bramkamp; Jochen Graw; Henning Hintzsche (BIOspektrum, 2022)

Aktuell - Ulrich Dobrindt; Jochen Graw; Henning Hintzsche (BIOspektrum, 2022)

Aktuell - Daniel Unterweger; Jochen Graw; Henning Hintzsche (BIOspektrum, 2022)

Journal Club - Andreas Seiffert-Störiko; Jörg Stülke; Victor Sourjik; Jonathan Wolf Mueller; Jürgen Lassak; Daniela Kruck; Katja Taute; Johannes Sander; Bettina Siebers; Jochen Graw (BIOspektrum, 2022)

Aktuell - Martin Pilhofer; Jochen Graw; Henning Hintzsche (BIOspektrum, 2022)

Buchrezension zu: The World Before Us - Jochen Graw (BIOspektrum, 2021)

Aktuell - Jürgen Lassak; Jochen Graw; Henning Hintzsche (BIOspektrum, 2021)

Aktuell - Natalia Tschowri; Jochen Graw; Daniela Kruck; Henning Hintzsche (BIOspektrum, 2021)

Journal Club - Jochen Graw; Harald Engelhardt; Kirsten Küsel; Daniela Kruck; Philip Tinnefeld; Johannes Sander; Silke Robatzek; Till F. Schäberle; Khadija Aichane; Ana Rita Brochado; David Gerlach (BIOspektrum, 2021)

Aktuell - Martin Baunach; Jochen Graw; Henning Hintzsche (BIOspektrum, 2021)

Buchrezension zu: Homo sapiens - Jochen Graw (BIOspektrum, 2021)

Journal Club - Jochen Graw; Klaus Hantke; Wolfgang Wohlleben; Christian Kost; Johannes Sander; Hanna Klimek; Khadija Aichane; Lena Brücker; Daniela Kruck; Justus Gräf (BIOspektrum, 2021)

Buchrezension zu: Darwins Hund - Jochen Graw (BIOspektrum, 2020)

Buchrezension zu: Die Reise unserer Gene - Jochen Graw (BIOspektrum, 2020)

Aktuell - Jürgen Lassak; Hagen Bachmann; Henning Hintzsche; Jochen Graw (BIOspektrum, 2020)

Journal Club - Wolfgang Wohlleben; Jochen Graw; Roland Benz; Johannes Sander; Jonathan Wolf Mueller; Christoph von Ballmoos; Miriam Herbert; Daniela Kruck; Martin Thanbichler; Gottfried Wilharm; Kai Thormann; Thilo M. Fuchs; et al. (BIOspektrum, 2020)

A comprehensive and comparative phenotypic analysis of the collaborative founder strains identifies new and known phenotypes - Heike Kollmus; Helmut Fuchs; Christoph Lengger; Hamed Haselimashhadi; Molly A. Bogue; Manuela A. Östereicher; Marion Horsch; Thure Adler; Juan Antonio Aguilar-Pimentel; Oana Veronica Amarie; Lore Becker; Johannes Beckers; et al. (Mammalian Genome, 2020)
The collaborative cross (CC) is a large panel of mouse-inbred lines derived from eight founder strains (NOD/ShiLtJ, NZO/HILtJ, A/J, C57BL/6J, 129S1/SvImJ, CAST/EiJ, PWK/PhJ, and WSB/EiJ). Here, we performed a comprehensive and comparative phenotyping screening to identify phenotypic differences and similarities between the eight founder strains. In total, more than 300 parameters including allergy, behavior, cardiovascular, clinical blood chemistry, dysmorphology, bone and cartilage, energy metabolism, eye and vision, immunology, lung function, neurology, nociception, and pathology were analyzed; in most traits from sixteen females and sixteen males. We identified over 270 parameters that were significantly different between strains. This study highlights the value of the founder and CC strains for phenotype-genotype associations of many genetic traits that are highly relevant to human diseases. All data described here are publicly available from the mouse phenome database for analyses and downloads.

Aktuell - Julia Vorholt; Philipp Keller; Tobias J. Erb; Hagen Bachmann; Henning Hintzsche; Jochen Graw (BIOspektrum, 2020)

Journal Club - Volkmar Braun; Georg Fuchs; Michael Schloter; Torsten Schubert; Jochen Graw; Daniela Kruck; Johannes Sander; Gerhart Drews; Stefan Schild; Klaus Hantke; Sandra Wiegand; Alexander Westermann; et al. (BIOspektrum, 2020)

Aktuell - Johannes Sander; Jochen Graw; Hagen Bachmann (BIOspektrum, 2019)

Journal Club - Jochen Graw; Lina Thoma; Hannah Jeckel; Knut Drescher; Bernhard Schink; Harald Engelhardt; Johannes Sander; Andreas Seiffert-Störiko; Tobias Engl; Michael Steinert; Martin Daus; Jannis Anstatt (BIOspektrum, 2019)

Mouse models for microphthalmia, anophthalmia and cataracts - Jochen Graw (Human Genetics, 2019)

Crybb2 Mutations Consistently Affect Schizophrenia Endophenotypes in Mice - Tamara Heermann; Lillian Garrett; Wolfgang Wurst; Helmut Fuchs; Valerie Gailus-Durner; Martin Hrabě de Angelis; Jochen Graw; Sabine M. Hölter (Molecular Neurobiology, 2019)

Journal Club - Bernhard Hube; Sascha Brunke; Christina Heil; Volkmar Braun; Alina Guse; Andreas Seiffert-Störiko; Christian Kähler; Gregor Witte; Ute Römling; Miriam Herbert; Daniela Kruck; Jochen Graw; et al. (BIOspektrum, 2019)

Aktuell - Marieke Scheffen; Hagen Bachmann; Jochen Graw (BIOspektrum, 2019)

Aktuell - Dirk Schüler; Hagen Bachmann; Jochen Graw (BIOspektrum, 2019)

Journal Club - Volkmar Braun; Jochen Graw; Wolfgang Buckel; Lennart Randau; Christian Kähler; Natalia Tschowri; Daniela Kruck; Jürgen Lassak; Jannis Anstatt; Pascal Meyer-Ahrens; Hannah Jeckel; Knut Drescher; et al. (BIOspektrum, 2019)

Aktuell - Knut Ohlsen; Hagen Bachmann; Henning Hintzsche; Jochen Graw (BIOspektrum, 2019)

Journal Club - Jochen Graw; Rebecca Halbach; Volkmar Braun; Lennart Randau; Johannes Sander; Andreas Seiffert-Störiko; Benedikt Moissl; Martin Daus; Martina Adamek; Fabian M. Commichau; Gerhart Drews; Jeroen S. Dickschat; et al. (BIOspektrum, 2019)

Aktuell - Oliver Kurzai; Hagen Bachmann; Henning Hintzsche; Jochen Graw (BIOspektrum, 2019)

Journal Club - Johannes Sander; Roman Iwasaki; Volkmar Braun; Blagovesta Popova; Christian Kähler; Julian Bender; Jan Muschiol; Klaus Hantke; Daniela Kruck; Frank Oliver Glöckner; Werner Liesack; Jana Deitersen; et al. (BIOspektrum, 2019)

Mikroorganismus in den Schlagzeilen Flavin-basierter extrazellulärer Elektronentransport bei Listerien - Gary Sawers; Jochen Graw; Hagen Bachmann; Henning Hintzsche (BIOspektrum, 2018)

Ausrottung der Anopheles-Mücken durch CRISPR-Cas9? - Jochen Graw; Wolfgang Buckel; Patrick Pausch; Gert Bange; Wolfgang Streit; Horst Lohrer; Martin Daus; Katrin Damm; Elisa Granato; Andreas Seiffert-Störiko (BIOspektrum, 2018)

Fgf9 Y162C Mutation Alters Information Processing and Social Memory in Mice - Lillian Garrett; Lore Becker; Jan Rozman; Oliver Puk; Tobias Stoeger; Ali Önder Yildirim; Alexander Bohla; Oliver Eickelberg; Wolfgang Hans; Cornelia Prehn; Jerzy Adamski; Thomas Klopstock; et al. (Molecular Neurobiology, 2018)

Crybb2 coding for βB2-crystallin affects sensorimotor gating and hippocampal function - Minxuan Sun; Sabine M. Hölter; Jens Stepan; Lillian Garrett; Just Genius; Elisabeth Kremmer; Martin Hrabě de Angelis; Wolfgang Wurst; D. Chichung Lie; Laure Bally-Cuif; Matthias Eder; Dan Rujescu; et al. (Mammalian Genome, 2013)

Lens density tracking in mice by Scheimpflug imaging - Oliver Puk; Martin Hrabĕ de Angelis; Jochen Graw (Mammalian Genome, 2013)

Longitudinal fundus and retinal studies with SD-OCT: a comparison of five mouse inbred strains - Oliver Puk; Martin Hrabĕ de Angelis; Jochen Graw (Mammalian Genome, 2013)

Innovations in phenotyping of mouse models in the German Mouse Clinic - Helmut Fuchs; Valérie Gailus-Durner; Susanne Neschen; Thure Adler; Luciana Caminha Afonso; Juan Antonio Aguilar-Pimentel; Lore Becker; Alexander Bohla; Julia Calzada-Wack; Christian Cohrs; Anna Dewert; Barbara Fridrich; et al. (Mammalian Genome, 2012)

Der Januskopf der genetischen Diagnostik - Jochen Graw (BIOspektrum, 2011)

Erratum to: Mouse models of cataract - Jochen Graw (Journal of Genetics, 2010)

Microphthalmia, parkinsonism, and enhanced nociception in Pitx3 416insG mice - Michael Rosemann; Alesia Ivashkevich; Jack Favor; Claudia Dalke; Sabine M. Hölter; Lore Becker; Ildikó Rácz; Ines Bolle; Martina Klempt; Birgit Rathkolb; Svetoslav Kalaydjiev; Thure Adler; et al. (Mammalian Genome, 2010)

Mouse models of cataract - Jochen Graw (Journal of Genetics, 2009)

Variations of eye size parameters among different strains of mice - Oliver Puk; Claudia Dalke; Jack Favor; Martin Hrabé de Angelis; Jochen Graw (Mammalian Genome, 2006)

Mapping of a novel MEN-like syndrome locus to rat Chromosome 4 - Kamilla Piotrowska; Natalia S. Pellegata; Michael Rosemann; Andreas Fritz; Jochen Graw; Michael J. Atkinson (Mammalian Genome, 2004)

V76D mutation in a conserved gD-crystallin region leads to dominant cataracts in mice - Jochen Graw; Jana Löster; Dian Soewarto; Helmut Fuchs; André Reis; Eckhard Wolf; Rudi Balling; Martin Angelis (Mammalian Genome, 2002)